Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Vertex
y = -(x + 3)² + 1
y = -(x + 3)(x + 3) + 1
y = -(x² + 3x + 3x + 9) + 1
y = -(x² + 6x + 9) + 1
y = -x² - 6x - 9 + 1
y = -x² - 6x - 8
-x² - 6x - 8 = 0
x = -(-6) +/- √((-6)² - 4(-1)(-8))
2(-1)
x = 6 +/- √(36 - 32)
-2
x = 6 +/- √(4)
-2
x = 6 +/- 2
-2
x = 6 + 2 x = 6 - 2
-2 -2
x = 8 x = 4
-2 -2
x = -4 x = -2
y = -x² - 6x - 8
y = -(-4)² - 6(-4) - 8
y = -(16) + 24 - 8
y = -16 + 24 - 8
y = 8 - 8
y = 0
(x, y) = (-4, 0)
or
y = -x² - 6x - 8
y = -(-2)² - 6(-2) - 8
y = -(4) + 12 - 8
y = -4 + 12 - 8
y = 8 - 8
y = 0
(x, y) = (-2, 0)
Axis of Symmetry
The axis of symmetry is equal to -3.
y = -(x + 3)² + 1
y = -(x + 3)(x + 3) + 1
y = -(x² + 3x + 3x + 9) + 1
y = -(x² + 6x + 9) + 1
y = -x² - 6x - 9 + 1
y = -x² - 6x - 8
-x² - 6x - 8 = 0
x = -(-6) +/- √((-6)² - 4(-1)(-8))
2(-1)
x = 6 +/- √(36 - 32)
-2
x = 6 +/- √(4)
-2
x = 6 +/- 2
-2
x = 6 + 2 x = 6 - 2
-2 -2
x = 8 x = 4
-2 -2
x = -4 x = -2
y = -x² - 6x - 8
y = -(-4)² - 6(-4) - 8
y = -(16) + 24 - 8
y = -16 + 24 - 8
y = 8 - 8
y = 0
(x, y) = (-4, 0)
or
y = -x² - 6x - 8
y = -(-2)² - 6(-2) - 8
y = -(4) + 12 - 8
y = -4 + 12 - 8
y = 8 - 8
y = 0
(x, y) = (-2, 0)
Axis of Symmetry
The axis of symmetry is equal to -3.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.